A passion for wisdom a very brief history of philosophy - Solomon, Robert C. 1942-2007; Higgins, Kathleen Marie 1954- (Oxford Univ. Press, 1997)
Readers eager to acquire a basic familiarity with the history of philosophy but intimidated by the task will find in A Passion for Wisdom: A Very Brief History of Philosophy a lively, accessible, and highly enjoyable tour of the world's great ideas. Without simplifying their subject, Robert Solomon and Kathleen Higgins tell the story of philosophy's development with great clarity and refreshing wit. The brevity of their study, in fact, allows readers to see more clearly the connections and divergences between philosophers, as well as the way ideas change, reappear, and evolve over time. The authors begin with the most ancient religious beliefs and bring us right up to the feminist and multicultural philosophies of the present. Along the way, major philosophers are highlighted, from Plato and Aquinas to William James and Simone deBeauvoir, and major categories explored, from metaphysics and ethics to politics and logic.
Keywords: Geschichte; Philosophie; Philosophy -- History; Einführung